Impact of facilitation on cognitive flow in a novel diabetes management rehearsal game for health professions education: mixed methods, open-label, superiority randomized controlled trial - Tan, Jun Wen (2024)
Background: Though the prevalence of diabetes is set to increase, most serious game solutions typically target patient self-management and education. Few games target health care professions education, and even fewer consider the factors that may increase their efficacies. The impact of facilitation, a prominent feature of health professions education, is examined in the context of a rehearsal-based diabetes management serious game. Objective: In this mixed methods, open-label, superiority randomized controlled trial, we compare student performance, attitudes, and perceptions of a rehearsal-based diabetes management game for health care professionals. Methods: Student participants were randomized into 2 groups to play a diabetes management game. The control group played the game alone, and the intervention group played the same game alongside a facilitator tasked to moderate overall challenge levels and address queries. Both groups were administered the Flow Short Scale, a 13-item measure rated on a 7-point Likert scale ranging from 1 (“not at all”) to 7 (“very much”) immediately after the game. Students were then invited to voluntary focus group discussions to elicit their attitudes and perceptions of the game. Findings were subject to between-group comparisons and inductive thematic analysis respectively. Results: A total of 48 (26 control, 22 intervention) clinical-year undergraduates from the Lee Kong Chian School of Medicine in Singapore participated in this study, with 18 continuing to the focus group discussions. Flow Short Scale results indicated the superiority of the intervention group for overall flow (t46=–2.17, P=.04) and the absorption subdomain (t46=–2.6, P=.01). Qualitative results indicated students viewed facilitation as helpful and appropriate, and were able to identify improvable elements of the game’s theoretical foundations and overall design. Conclusions: While serious games are efficacious means of rehearsing previously learned knowledge, facilitation allows for their efficiency to be greatly increased. Such increases are likely crucial in the coming years with the increased digitization of health care professions education and the prevalence of diabetes.